Economic Growth and Judicial Independence: Cross Country Evidence Using a New Set of Indicators - Lars P. Feld; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2003)
Rational politicians are interested in judicial independence (JI) in order to make their promises credible. But if politicians' preferences deviate from the dicta of the judiciary, they also have incentives to renege on judicial independence. These two conflicting aspects are measured by two indicators: (i) de iure JI focusing on its legal foundations and (ii) a de facto JI focusing on countries' actually experience. Whether JI affects economic growth is tested for a cross section of 57 countries. While de iure JI does not have an impact on real GDP growth per capita growth, de facto JI positively influences it.
Keywords: 330; economic growth; rule of law; judicial independence